A Comprehensive Outcome Review of Subfascial Breast Augmentation over a 10-Year Period. Issue 6 (December 2020) - Brown, Tim
Abstract : Background: Subfascial placement of breast implants has the advantages of subglandular and submuscular placement without the adverse outcomes. There are few large series with longitudinal follow-up and outcome measures. Methods: Seven hundred eighty-three patients underwent subfascial breast augmentation and were followed up for 10 years. Adverse outcomes, changes in breast morphometry, and patient satisfaction were outcome measures. Results: All morphometry increased except soft-tissue thickness at the lateral sternal margin. The distance from the nipple-areola complex to the inframammary crease increased by 40 percent, with a concomitant 6.2 percent increase in the distance from the suprasternal notch to the nipple-areola complex. The capsular contracture rate was 6.48 percent, and correlates with a lateral sternal margin of less than 20 mm ( r = 0.57, p < 0.001). Ripples occurred in patients with less than 10 mm of soft tissue at the lateral sternal margin; 11.6 percent of patients would choose a larger implant and 2.7 percent would choose a smaller implant. Conclusions: Subfascial placement of breast implants provides a reliable technique. It can be used in patients with at least 20 mm of soft tissue at the lateral sternal margin. Those with 10 to 20 mm should be counseled that ripples may occur if they lose body fat. The technique is unsuitable for individuals with less than 10 mm measurable at the lateral sternal margin. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.